Pengembangan Media Kuartet Card melalui Metode Think Talk Write untuk Meningkatkan Keterampilan Menulis Teks Prosedur Siswa Kelas IV SD - Adristya, Ananta Sely; SB, Nugraheti Sismulyasih (Paedagogie, 2026)
This research was motivated by the suboptimal writing skills of fourth grade elementary school students. The purpose of this study was to develop a Quartet Card media design using the Think Talk Write method, to test its feasibility, and to test its effectiveness in improving fourth grade students' procedural text writing skills at Jatisari Elementary School. The research used was Research and Development (R&D). The development model used refers to the Borg and Gall model, simplified into eight stages: 1) research and information gathering; 2) planning; 3) developing the initial product; 4) limited testing; 5) revising the initial product; 6) field testing or large-scale testing; 7) revising the final product; 8) dissemination and implementation. Data collection techniques include tests (pretest and posttest) and non-tests (observation, interviews, questionnaires and documentation). Data analysis techniques consist of initial data analysis using the Normality test and final data analysis using the paired sample t-test and the N-Gain test. The results of the feasibility test obtained a percentage of assessments from material expert validators of 98.3% and media experts of 95%, so it is categorized as very feasible. The effectiveness of the Quartet Card media through the Think Talk Write method is proven through a T test which shows a significance value of 0.000 (p <0.005) which means there is a significant difference between the ability to write procedural texts before and after treatment, in addition the N-Gain value also shows a value of 0.6389 on a small scale and 0.6976 on a large scale which indicates a moderate category. From these results, it can be concluded that the Quartet Card media through the Think Talk Write method is stated to be very feasible to use in learning to write procedural texts. Thus, the development of Quartet Card media through the Think Talk Write method is feasible and effective for improving the procedural text writing skills of fourth-grade students at Jatisari Elementary School.